IN THE PEDAGOGICAL ACTIVITY OF THE TEACHER PSYCHOLOGICAL BARRIERS AND METHODS OF THEIR ELIMINATION - Ortiqova Nargiza Akramovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes some of the psychological problems faced by the teacher in his pedagogical activity and shows methodological directions for their elimination.